Precision oncology in urothelial cancer. (3rd March 2020) - Liow, Elizabeth; Tran, Ben
Abstract : Genomics-driven, precision medicine has been adopted in virtually every tumour type and underlies the significant advances in cancer management to date. The paradigm shift from the indiscriminate use of chemotherapeutics, to strategies that harness our mechanistic knowledge of cancer biology has led to profound clinical benefit for patients, and will continue to mould present and future treatment approaches. In the realm of urothelial cancer, the present status of precision medicine includes a rich landscape that encompasses molecularly-matched therapy, predictive biomarkers that could help inform response to chemotherapy and immunotherapy, as well as novel strategies such as antibody drug conjugates that exploit the use of target proteins for enhanced tumour killing. Here, we present an overview on these clinically-impactful discoveries in urothelial cancer, discuss the limitations and challenges in the implementation of precision oncology, and offer our vision for its future.